BIAYA RAWAT JALAN DAN RAWAT INAP DI RUMAH SAKIT PADA PASIEN DIABETES MELITUS - Ricko Pratama Ridzkyanto (Al Tamimi Kesmas: Jurnal Ilmu Kesehatan Masyarakat (Journal of Public Health Sciences), 2025)
Diabetes mellitus impacts the quality of human resources and significantly increases healthcare costs. This study aimed to determine the costs of outpatient and inpatient care in hospitals for diabetes mellitus patients. This study used BPJS Kesehatan sample data from 2015 to 2023, followed by univariate analysis. The total cost required for outpatient care for diabetes mellitus patients in hospitals is <1,000,000, while for inpatient care for diabetes mellitus patients in hospitals is between 1,000,000 and 5,000,000